Mixed convection from semi-circular cylinder in Bingham plastic fluids: Adding buoyancy. (2022) - Gupta, Anjali; Iyer Ganesh, Krutika; Melnik, Roderick; Kumar Tiwari, Anurag
Abstract: Mixed convection heat transfer from a heated semi-circular cylinder in Bingham plastic fluids with adding buoyancy configuration has been studied numerically. Extensive results of fluid flow and heat transfer characteristics are presented in terms of the velocity and temperature profiles, shape and size of yield/unyielded zone. In the steady flow regime, Reynolds number, Prandtl number, and Richardson number are expected to be positively dependent on the average Nusselt number (which decreases the convection boundary layer). In contrast, the average Nusselt number decreases as the value of the Bingham number increases from its maximum value in Newtonian media to its conduction limit when most of the fluid is frozen.. Finally, using a simple expression, the numerical results of average Nusselt number have been predicted in terms of the j -factor for new applications.